The Representation of Sexuality in the Film Dua Garis Biru (A Cinematic Narrative and Media Aesthetic Analysis) - Varlina, Vivi; Siahaan, Sintya Verawati; Kavka, Alya (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2024)
Film is a cinematographic work that not only presents captivating audiovisual elements but also serves as a medium for artistic and cultural expression, often addressing important issues. Dua Garis Biru is a film that boldly tackles social issues still considered taboo in Indonesia, such as early marriage and sexual education. This research aims to analyze the representation of these issues through the character Dara, using a semiotic approach. The focus is on how audiovisual elements—narrative, visuals, and sound—contribute to conveying messages about sexuality and sexual education within the social and cultural context of Indonesia. The research method employed is qualitative, involving an in-depth analysis of cinematic narrative and media aesthetics. The findings explore how Dua Garis Biru portrays issues of sexuality outside the context of marriage through dialogue, visual symbols, and the use of sound elements that strengthen characterization and atmosphere, providing deeper insight into the themes presented in the film.